Bima Swarga in Balinese Wayang - Hinzler, H. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1981)
The aim of the author's research was to study 1) the thematic elements and the composition of the plays (lelampahan wayang), and 2) their religious and cultural background. She concentrates on one particular play: the story of Bima Swarga. The study is based mainly on fieldwork carried out in Bali over the period 1972- 1976, when materials were collected from oral and written sources.